Degeneracy effect of dynamical properties of quasi-particles of electronic origin in semiconductor materials - Suprun, A.D.; Shmeleva, L.V. (Functional Materials, 2012)
The general dynamical properties of free quasi-particles are analyzed. Analyzed also the conditions under which the description of the dynamic properties of the quasi-particles is almost identical with those of real relativistic particles. The problem of the relation of quantum and classical methods of describing the quasi-particles in the case of the excited states of crystals is considered. Basic principles of construction of dynamic properties of classic type for quasi-particles at excitation of matter with the structure of solids (crystals) are analyzed. The results of analysis were demonstrated on the example of electronic excitations of crystals in the simplest case, when other effects are neglected (phonons, the response to excitation of the lattice, defects, high density of excitations, which requires the account of interactions between them, and so forth). It was shown that such excitations are described in three ways simultaneously. These descriptions make it possible to interpret the experimental data in terms of the usual relativistic dynamics, if the considered system allows the use of the considered approximations (plane wave in a phase, nearest neighbors and cubic grate).